Interactions between three biological control agents of water hyacinth, Eichhornia crassipes (Mart.) Solms (Pontederiaceae) in South Africa - Petela, Nomvume (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2018)
Water hyacinth, Eichhomia crassipes (Mart.) Solms (Pontederiaceae) is a free-floating perennial weed that is regarded as the worst aquatic weed in the world because of its negative impacts on aquatic ecosystems. It is native to the Amazon Basin of South America, but since the late 1800s has spread throughout the world. The first record of the weed in South Africa was noted in 1908 on the Cape Flats and in KwaZulu-Natal, but it is now dispersed throughout the country. Mechanical and chemical control methods have been used against the weed, but biological control is considered the most cost-effective, sustainable and environmentally friendly intervention. Currently, nine biological control agents have been released against water hyacinth in South Africa, and Neochetina eichhorniae Warner (Coleoptera: Curculionidae) is used most widely to control it. However, in some sites, water hyacinth mats have still not been brought under control because of eutrophic waters and cool temperatures. It was therefore necessary to release new biological control agents to complement the impact of N. eichhorniae. Megamelus scutellaris Berg (Hemiptera: Delphacidae) was released in 2013, but little is known about how it interacts with other agents already present in South Africa. It is likely to compete with the established biological control agent, Eccritotarsus eichhorniae Henry (Heteroptera: Miridae), because they are both sap suckers. On the other hand, N. eichhorniae is the most widespread and thus the most important biological control agent for water hyacinth. The aim of this study, then, was to determine the interactions between the two sap-sucking agents in South Africa that presumably occupy similar niches on the plant, and the interaction between M. scutellerais and N. eichhorniae, the most widely distributed and abundant agent in South Africa. Three experiments were conducted at the Waainek Research Facility at Rhodes University, Grahamstown, Eastern Cape, South Africa. Plants were grown for two weeks and insect species were inoculated singly or in combination. Water hyacinth, plant growth parameters and insect parameters were measured every 14 days for a period of 12 weeks. The results of the study showed that feeding by either E. eichhorniae or M. scutellaris had no effect on the feeding of the other agent. Both agents reduced all the measured plant growth parameters equally, either singly or in combination (i.e. E. eichhorniae or M. scutellaris alone or together). The interaction between the two agents appears neutral and agents are likely to complement each other in the field. Prior feeding by E. eichhorniae or M. scutellaris on water hyacinth did not affect the subsequent feeding by either agent. Megamelus scutellaris prefers healthy fresh water hyacinth plants. In addition, planthoppers performed best in combination with the weevil, especially on plants with new weevil feeding scars. The results of the study showed that M. scutellaris is compatible with other biological control agents of water hyacinth that are already established in South Africa. Therefore, the introduction of M. scutellaris may enhance the biological control of water hyacinth in South Africa.
Keywords: Water hyacinth -- South Africa; Water hyacinth -- Biological control -- South Africa; Aquatic weeds -- Biological control -- South Africa; Curculionidae; Delphacidae; Miridae; Neochetina eichhorniae Warner; Megamelus scutellaris Berg; Eccritotarsus eichhorniae Henry